2019
DOI: 10.18689/mjaes-1000103
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Tillage and Organic Matter management on Soil Structure

Abstract: Organic materials are important resources for the improvement of soil physical and chemical properties. This study was carried out to examine the impact of tillage and organic matter on some soil structural indices. The study was designed in a split-plot Randomized Complete Block with four replications. Hoe tillage and no-tillage were assigned to the main plot, whilst the subplot comprised cowpea residue, cattle manure, maize residues, elephant grass and control (no organic residue applied). The soil physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…These results indicate that CT operations can significantly decrease bulk density at least in the short term, consequently increasing as time from tillage operation further increases through the crop season (Telak et al., 2020). Regarding temporal outcomes for RT, OT and NT, they coincided with studies where no significant short to long‐term effects of tillage on bulk density under conservation tillage systems have been reported (Dao, 1996; Khalid et al., 2019; Martínez et al., 2008). Averages for the sum of data for both phases to analyse differences in bulk density by tillage showed a significant variation mainly as a result of the lower (rather stable for both experimental phases) bulk density value on OT.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These results indicate that CT operations can significantly decrease bulk density at least in the short term, consequently increasing as time from tillage operation further increases through the crop season (Telak et al., 2020). Regarding temporal outcomes for RT, OT and NT, they coincided with studies where no significant short to long‐term effects of tillage on bulk density under conservation tillage systems have been reported (Dao, 1996; Khalid et al., 2019; Martínez et al., 2008). Averages for the sum of data for both phases to analyse differences in bulk density by tillage showed a significant variation mainly as a result of the lower (rather stable for both experimental phases) bulk density value on OT.…”
Section: Resultssupporting
confidence: 79%
“…These results indicate that CT operations can significantly decrease bulk density at least in the short term, consequently increasing as time from tillage operation further increases through the crop season (Telak et al, 2020). Regarding temporal outcomes for RT, OT and NT, they coincided with studies where no significant short to long-term effects of tillage on bulk density under conservation tillage systems have been reported (Dao, 1996;Khalid et al, 2019;Martínez et al, 2008).…”
Section: Dry Bulk Densitysupporting
confidence: 70%
“…In our study, the effect of organic matter from maize and bean residues was linked to the mineral constituents of a sandy soil. The results showed a slight similarity with the works of Gupta et al (1987) and Guerif and Faure (1979), but differed from those obtained by Khalid et al (2019). However, they studied total porosity in a field experiment.…”
Section: Soil Structural Voids Ratio (E S )supporting
confidence: 67%
“…Guerif (1990) found that soil aggregation could be related to the effect due to the interaction of agents such as organic matter and clay content. Khalid et al (2019) conducted an experiment with maize and cowpea mulch incorporated into the soil with a hoe to evaluate the effect of these residues on soil properties, They found that bean straw produced higher total porosity than corn (49.28% against 47.95%). However, the difference was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tillage breaks macro-aggregates and exposes protected OM "inside the aggregates" to microbial decay [59,141]. Consequently, reducing soil disturbance can provide a potential to reduce SOC degradation by increasing its protection either inside the macro-aggregates or maintaining it on the soil surface [2,59,66,68,142]. This explanation has been supported by the significant increase in the portion of SOC inside macro-aggregates [26,59], wherein some estimates indicated that the most SOC (more than 75%) was stocked into macroaggregates [71,143].…”
Section: Effect Of Tillage On Socmentioning
confidence: 99%